Theoretical analysis and simulation of FTIR spectrometer based on rotating double-sided reflective mirror - Yinhui Tang; Peidong He; Yu Zhang; Jianwei Wang; Yang Bai; Qunbo Lv (Results in Physics, 2024)
In this study, the FTIR spectrometer-based rotating double-sided reflective mirror (RDRM) is presented. By introducing the RDRM and corner reflector, an optical path difference (Opd) is generated between the two separated light beams. The instrument is highly stable. Spectral restoration is achieved by the scale, which is precalculated using a laser interferogram. This method suppresses the influence of non-linearity and inherent errors on the restored spectrum. We elaborate on this principle through a theoretical analysis and simulation. Based on a set of design parameters, we successfully restored the spectrum with spectral resolution of 0.25 cm−1 through scale in the case of error (average is –13.88 μm and the mean square deviation is 5.7 μm). The relative spectral mean square error (SMSE) is 0.0013 and the spectral correlation coefficient (SCC) is 0.9997.